Sci-Tech Libraries Serving Zoological Gardens, 1st edition - Mount, Ellis (Routledge, 2020)
In response to the general lack of information about zoo libraries, this book, first published in 1988, compiles a collection of descriptions of the libraries serving six American zoos. The accounts of zoo libraries include the National Zoological Park in Washington, DC, the Lincoln Park Zoo in Chicago, and the Minnesota Zoological Garden Library in St. Paul. The contributors detail the types of collections and services offered at zoo libraries. In addition, a survey made of 78 American zoo libraries is included, including information about their staffs, facilities, collections, and services, as well as data on 32 archive collections.